Ozone Sensitive Properties of Thin Films of Nanocrystalline Silicon Carbide - Semenov, A. V.; Lubov, D. V.; Makhonin, M. V. (Cумський державний університет, 2020)
In this paper, we investigated the ability of nanocrystalline SiC films to detect ozone in an air mixture under atmospheric pressure for ozone concentrations of 0.1 mg/m3 (maximum allowable concentration) and 4.0 mg/m3. The ozone sensitivity coefficient S (О3) was estimated by the formula S (О3) = (Rg – Ra)/Ra, where Rg and Ra are respectively the film resistances in the presence and absence of ozone in the air atmosphere. The volume flow rate of the ozone-air mixture was 2 l/min. The temperature dependence of the ozone sensitivity coefficient S (O3) was studied in the temperature range 100-450 ºC. It was found that the maximum values of S (O3) + 0.71 and – 0.80 were observed at temperatures of 280 ºC and 330 ºC, respectively, for both concentrations of ozone. Moreover, S (O3) had a positive sign for a temperature of 280 ºC and a negative value for 330 ºC. The different polarity of the change in the film resistance at given temperatures was due to the different ratio of redox reactions of ozone with atmospheric gases on the surface of nc-SiC films. Both temperatures can be used for detecting ozone with sensors on nc-SiC films, however, from the point of view of reducing energy consumption, operating temperature of 280 ºС looks more preferable.

У роботі ми дослідили здатність нанокристалічних плівок SiC виявляти озон у атмосферній суміші під атмосферним тиском за концентраціями озону 0,1 мг/м3 (максимально допустима концентрація) та 4,0 мг/м3. Коефіцієнт чутливості до озону S (О3) оцінювали за формулою S (О3) = (Rg – Ra)/Ra, де Rg і Ra– плівкові опори при наявності та відсутності озону в атмосфері повітря відповідно. Об'ємна витрата озоно-повітряної суміші становила 2 л/хв. Вивчено температурну залежність коефіцієнта чутливості до озону S (O3) в інтервалі температур 100-450 ºС. Було встановлено, що максимальні значення S (O3) + 0,71 та – 0,80 спостерігалися при температурах 280 ºС та 330 ºС відповідно для обох концентрацій озону. Крім того, встановлено, що S (O3) мав позитивний знак при температурі 280 ºС і негативне значення при 330 ºС. Різна полярність зміни опору плівки при заданих температурах була обумовлена різним співвідношенням окислювально-відновлювальні реакції озону з атмосферними газами на поверхні плівок nc-SiC. Обидві температури можна використовувати для детектування озону за допомогою датчиків на плівках nc-SiC, однак, з точки зору зниження споживання енергії, температура 280 ºС виглядає більш переважно.
Озоночутливі властивості тонких плівок нанокристалічного карбіду кремнію
Keywords: ozone sensors; silicon carbide; nanocrystalline film; electrical resistance; temperature ozone sensitivity; сенсор озону; карбід кремнію; нанокристалічні плівки; електричний опір; температурна залежність